Combined kidney and hematopoietic stem cell transplantation from the same donor: systematic review of clinical outcomes and limitations - Modelska, Julia; Sadowski, Krzysztof; Miedziaszczyk, Miłosz; Corona Deschamps, Axel; Idasiak-Piechocka, Ilona (Journal of Medical Science, 2026)
Background. Kidney transplantation is the most effective method of renal replacement therapy. The consequence of a conventional transplant is the need to use immunosuppressive drugs throughout life, which is associated with many side effects. A possible strategy for avoiding immunosuppressive therapy may be kidney transplantation from the same donor after hematopoietic cell transplantation (HSCT) or bone marrow transplantation (BMT). Material and methods. A systematic literature search was conducted in the PubMed, Scopus, Web of Science, and Cochrane databases using various combinations of keywords related to simultaneous or sequential kidney and bone marrow (or hematopoietic stem cell) transplantation from the same donor.Results. Combined kidney and hematopoietic stem cell transplantation from the same donor has shown promising results, particularly in HLA-matched recipients, enabling withdrawal of immunosuppressive therapy without rejection. In HLA-mismatched cases, success was observed mainly with intensive conditioning regimens (e.g., total lymphoid irradiation, antithymocyte globulin, fludarabine). Early outcomes often included stable graft function and absence of acute rejection, but long-term follow-up revealed risks such as chronic rejection and declining renal function.Conclusions. Despite encouraging outcomes, the approach remains experimental due to the lack of standardised protocols, validated biomarkers, and a complete understanding of chimerism persistence. Further clinical trials with long-term follow-up are needed to identify predictors of success, optimise conditioning strategies, and evaluate safety. The method holds potential, especially for patients with hematologic malignancies, but routine clinical application is not feasible.
Keywords: kidney transplantation; hematopoietic stem cells transplantation; transplantation tolerance; chronic kidney disease; bone marrow transplantation